Late Pleistocene to Holocene variations in marine productivity and terrestrial material delivery to the western South Atlantic - Dauner, Ana Lúcia Lindroth; Mollenhauer, Gesine; Hefter, Jens; Bícego, Márcia Caruso; de Mahiques, Michel Michaelovitch; Martins, César de Castro (Frontiers in Marine Science, 2022)
Despite the increased number of paleoceanographic studies in the SW Atlantic in recent years, the mechanisms controlling marine productivity and terrestrial material delivery to the South Brazil Bight remain unresolved. Because of its wide continental shelf and abrupt change in coastline orientation, this region is under the influence of several environmental forcings, causing the region to have a large variability in primary production. This study investigated terrestrial organic matter (OM) sources to, and marine OM sources in the South Brazil Bight, and the main controls on marine productivity and terrestrial OM export. We analyzed OM geochemical (bulk and molecular) proxies in sediment samples from a core (NAP 63-1) retrieved from the SW Atlantic slope (24.8° S, 44.3° W, 840 m water depth). The organic proxies were classified into “terrestrial-source” and “marine-source” groups based on a cluster analysis. The two sources presented different stratigraphical profiles, indicating distinct mechanisms governing their delivery. Bulk proxies indicate the predominance of marine OM, although terrestrial input also affected total OM deposition. The highest marine productivity, observed between 50 and 39 ka BP, was driven by the combined effects of the South Atlantic Central Water upwelling promoted by Brazil Current eddies and fluvial nutrient inputs from the adjacent coast. After the last deglaciation, decreased phytoplankton productivity and increased archaeal productivity suggest a stronger oligotrophic Tropical Water presence. The highest terrestrial OM accumulation occurred between 30 and 20 ka BP, with its temporal evolution controlled mainly by continental moisture evolution. Sea level fluctuations affected the distance between the coastline and the sampling site. In contrast, continental moisture affected the phytogeography, changing from lowlands covered by grasses and saltmarshes to a landscape dominated by mangroves and the Atlantic Forest. Our results suggest how the OM cycle in the South Brazil Bight may respond to warmer and dryer climate conditions.